Jan Paweł II jako romantyk. Uwagi na marginesie papieskich odwołań do dzieł Adama Mickiewicza = John Paul II as a romantic poet. Notes on a fringe of papal recollections of Adam Mickiewicz masterpieces - Kulesza, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main purpose of this article was to analyse and select from the extensive matter of papal statemenst, homilies, speeeches and letters references to the Works of Adam Mickiewicz. On the basis of these references to the most famous Polish poet one can observe that for John Paul II the literature is subordinate to the spirituals and theological content.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; twórczość literacka; literary work; Polska; Poland; 20 w.